Permasalahan dalam Penerapan Mekanisme Pasar Perspektif Islam - Tri Wahyuni (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2019)
The market is a place for economic activity where economic activities take place naturally so that the rules of the game occur naturally. So according to Islamic economics the market mechanism can occur naturally from the supply and demand side as it should. Furthermore, in terms of the market mechanism of the Islamic economic perspective, in principle, it rejects the existence of a price intervention if price changes occur because the market mechanism is reasonable. However, the market here requires morality, among others: fair competition, honesty, transparency and justice. If these values ​​have been enforced, there is no reason to reject market prices. And if there is a deviation, the state's obligation to regulate it is for the benefit of the people.